Epistemology of Hadith: Orientation for Chapters Compilation in the Kutub Sittah - Ulama'i, Hasan Asy'ari; Muhtarom, Muhtarom; Mundhir, Mundhir (Jurnal Theologia, 2022)
This paper examines the epistemology of hadith, namely the orientation and background of the arrangement of the "chapters" in the Kutub Sittah. More specifically, this paper is directed at answering questions: 1) what is the background and orientation of the Kutub Sittah chapters arranged, and 2) how is the order of the books/chapters arranged? Through the descriptive analysis method, this study concludes; 1) the chapters in the Kutub Sittah were compiled by the compilers to serve as a guide for Muslims in following the sunnah of the Prophet, and to make it easier for them to obtain answers to their problems based on the sunnah of the Prophet; 2) The Kutub Sittah compiles its hadiths based on fiqh chapters so that the naming of Sunan in the works of Abu Dawud, at-Tirmidhi, an-Nasa'i, and Ibn Majah is very fitting. The work of al-Bukhari and Muslim is called Jami' because there is the addition of a special discussion, namely the chapters of faith, knowledge, fadhilah, tafsir, and manaqib.